Integrating data‐deficient species in analyses of evolutionary history loss. Issue 23 (1st November 2016) - Veron, Simon; Penone, Caterina; Clergeau, Philippe; Costa, Gabriel C.; Oliveira, Brunno F.; São‐Pedro, Vinícius A.; Pavoine, Sandrine
Abstract: There is an increasing interest in measuring loss of phylogenetic diversity and evolutionary distinctiveness which together depict the evolutionary history of conservation interest. Those losses are assessed through the evolutionary relationships between species and species threat status or extinction probabilities. Yet, available information is not always sufficient to quantify the threat status of species that are then classified as data deficient. Data‐deficient species are a crucial issue as they cause incomplete assessments of the loss of phylogenetic diversity and evolutionary distinctiveness. We aimed to explore the potential bias caused by data‐deficient species in estimating four widely used indices: HEDGE, EDGE, PDloss, and Expected PDloss. Second, we tested four different widely applicable and multitaxa imputation methods and their potential to minimize the bias for those four indices. Two methods are based on a best‐ vs. worst‐case extinction scenarios, one is based on the frequency distribution of threat status within a taxonomic group and one is based on correlates of extinction risks. We showed that data‐deficient species led to important bias in predictions of evolutionary history loss (especially high underestimation when they were removed). This issue was particularly important when data‐deficient species tended to be clustered in the tree of life. The imputation method based on correlates of extinction risks, especially geographic range size, had the best performance and enabled us to improve risk assessments. Solving threat status of DD species can fundamentally change our understanding of loss of phylogenetic diversity. We found that this loss could be substantially higher than previously found in amphibians, squamate reptiles, and carnivores. We also identified species that are of high priority for the conservation of evolutionary distinctiveness. Abstract : We tested how correctly indices of evolutionary history losses were calculated when data‐deficeint species were included thanks to 4 different methods. Including data‐deficient species by estimating their threat status thanks to trait proximity, especially in range size, enables to refine assessments of evolutuionary history loss. Likely probability of extinctions of DD species would cause the loss of large amounts of evolutionary history and those species may capture highly threatened evolutionary distinctiveness.